Dochody w gospodarstwach indywidualnych w okręgu środkowym zachodnim - Piasny, Janusz (Wydział Prawa i Administracji UAM, 1966)
The research work is based ori the results obtained from agricultural accountancy notes kept by approximately 140 peasant farms in the mid-western region. This region comprises almost the whole territory of the vaivodships of Poznań and Bydgoszcz. The results of study have been presented on the data of the following years: 1952/53, 1955/56, 1957/58, 1959/60, 1961/62 and l962/63. In the said periods of time the farms' incomes were changing chiefly under the influence of the following factors: the volume of production, the prices of agricultural produce, the obligation to the state and the revenues drawn from non- -agricultural occupations. The value of global production in the examined period has increased by 95% — thanks to the rise in the volume of crops and to the rise in procurement prices. The burden of obligation has decreased by 14°/o — especially in view of the reduced compulsory supply quotas, whereas the non-agricultural incomes have increased by 105%. All of those changes had a positive effect on the size of final incomes of peasant farms, rising them by l20%. The incomes falling on one member of peasant family reached in 1962/63 the amount of over 10 thousand zł., and were thus higher from the average income prevailing on a nationwide scale by 1800 zł. The earned incomes were always spent on consumption and production expenditures. In different periods various factors played, however, a decisive role in the way of spending incomes. Up to 1954/55, the prime factor in that respect were the consumption and not the production requirements. The accumulation at that time had been very small and even in the period of 1952/3 and 1953/54 a disaccumulation had taken place. It is only since 1956 that began a distinct but uneven rise in accumulation. This accumulation led to house construction activities, to the increase in livestock and farm equipment, to money saving habits and to the increase in stocks and reserves. In respect, however, to expenditures on renovations of melioration schemes, the examined farms showed for all the period in question only a limited reproduction. The accumulation in bigger farms is being derived mainly from agricultural income, whereas in the smaller and medium ones almost the whole accumulation has its origin in incomes drawn from non-agricultural occupations.
Income in Privately Owned Farms in the Mid-Western Region